Nurses on the move: Robert Wood Johnson Foundation nurse faculty scholars and their action on the social determinants of health. Issue 3 (3rd April 2019) - Ogbolu, Yolanda; Ford, Jodi; Cohn, Elizabeth; Gillespie, Gordon Lee
ABSTRACT: Objective: Medical care alone cannot adequately improve population health or eliminate inequities; social determinants of health (SDH) must be addressed. This study's purpose was to describe the research, teaching, service, and clinical practice activities implemented by RWJF Nurse Faculty Scholars to act on the SDH. Design: A cross-sectional survey design was used with a sample of RWJF Nurse Faculty Scholars, chosen because they were provided specialized mentoring, grants, and other support that allowed them to explore SDH. Results: Respondents ( n  = 57) addressed SDH in their research (86.0%), teaching (68.4%), service (66.7%), and clinical practice (33.3%). Leading research foci were quality of health care (56.1%), social and physical environmental stressors (54.4%), and access to health care services (49.1%). Leading SDH areas in teaching were discrimination in society against vulnerable populations (54.4%), quality of health care received by vulnerable populations (50.9%), and vulnerable populations' access to health care services (50.9%). Service activities included addressing discrimination against diverse populations. Leading SDH areas in clinical practice were quality of health care received by vulnerable populations (28.1%), vulnerable populations' access to health care services (22.8%), and discrimination in society against vulnerable populations (19.3%). Respondents also addressed SDH through personal mentoring (71.9%); efforts to recruit and/or retain underrepresented faculty (59.6%); developing a diverse pipeline of nurses (59.6%); and participation on a diversity committee (40.4%). Conclusion: The RWJF Nurse Faculty Scholars were able to leverage their awards to address SDH; however, further research is needed to assess the impact of the SDH work conducted. Knowledge from this study can be used as a road map for SDH elements and areas of professional work that nurses and other health professionals could address SDH in research, teaching, service, and practice.